Nanoencapsulation of amitriptyline enhances the potency of antidepressant-like effects and exhibits anxiolytic-like effects in Wistar rats. - Ramón Eduardo Valadez-Lemus; José L Góngora-Alfaro; Juana María Jiménez-Vargas; Javier Alamilla; Néstor Mendoza-Muñoz (PLoS ONE)
Depression poses a significant global health challenge, affecting an estimated 300 million people worldwide. While amitriptyline (Ami) remains one of the most effective antidepressants, its numerous side-effects contribute to a high dropout rate among patients. Addressing this issue requires exploring methods to enhance its bioavailability and reduce dosage. In this study, we describe a technique for producing amitriptyline nanoparticles (Ami-NPs) to improve the drug's efficiency. The effectiveness was assessed by comparing the dose-response curves of Ami-NPs and non-encapsulated Ami in male and female Wistar rats subjected to the forced swimming test (FST). Ami-NPs were fabricated using nanoprecipitation, with a copolymer of poly (methyl vinyl ether/maleic acid) as the encapsulant, and a 3% solution of poloxamer F-127 as surfactant stabilizer. A Box-Behnken design was used to optimize the production of Ami-NPs, resulting in nanoparticles with the following optimal characteristics: a size of 198.6 ±  38.1 nm, a polydispersity index of 0.005 ±  0.03 nm, a zeta potential of -32 ±  6 mV, and encapsulation efficiency of 79.1 ±  7.4%. Ami-NPs showed higher potency and efficacy in reducing immobility during the FST (ED50 =  7.06 mg/kg, Emax =  41.1%), compared to amitriptyline in solution (Ami-S) (ED50 =  11.89 mg/kg, Emax =  33.2%). The Emax of Ami-NPs occurred at 12 mg/kg, while Ami-S peaked at 15.8 mg/kg. In the open field test, only treatment with Ami-NPs (12 mg/kg) and the empty nanoparticles increased immobility. In the elevated plus-maze, treatment with Ami-NPs (12 mg/kg) significantly reduced closed-arm entries (2.1 ±  0.6), compared to control solution (9.5 ±  1.8), control nanoparticles (8 ±  1.0) and Ami-S (11.5 ±  2). In the marble burying test, Ami-NPs (12 mg/kg) significantly reduced buried marbles (2.4 ±  0.4) compared to control nanoparticles (8.7 ±  1.2). These findings suggest that Ami-NPs could be a promising approach to enhance Ami bioavailability, thereby increasing its potency and antidepressant efficacy, while improving anxiolytic-like effects.